Micropropagation of Rosaceous Species SAM Grown in Temperate Climate - Sedlak, Jiri; Paprstein, Frantisek (Methods in molecular biology (Clifton, N.J.), 2020)
The benefits of in vitro plant cultivation are mainly due to very high multiplication rate. Cultivation of plant material in vitro can be carried out during the whole year regardless of the time of the year or weather conditions. We create artificial conditions in the lab (heat, light, humidity), and we can regulate these conditions at any time. For the preservation of cultivar identity, we recommend establishing in vitro cultures from shoot tips usually larger than 0.2 mm. In practice, in vitro cultivation of plants uses these growth regulators to achieve organogenesis, for example, root formation, prolonged growth, or multiplication. During each subculture, these cultures are then transferred on a solid agar medium in the form of actively growing multiple shoots with a well-differentiated shoot tip containing meristematic area. Cytokinins are important for cell division and causes branching of plants. Auxins, both endogenous and exogenous, act at as a trigger for the differentiation and formation of root primordia. Morphological characteristics (formation of leaves or callus) and shoot development should be observed during in vitro multiplication and after transfer to ex vitro conditions.
Keywords: Plant Shoots; Culture Media; Media; Cell Proliferation; kultivační média; výhonky rostlin; techniky in vitro; regulátory růstu rostlin; Tissue Culture Techniques; kyseliny indoloctové; meristém; Rosaceae; techniky tkáňových kultur; Growth regulator; Cytokinins; Acclimatization; Meristem; cytokininy; Plant Growth Regulators; Indoleacetic Acids; In vitro; Explant; proliferace buněk; Multiplication rate; In Vitro Techniques; aklimatizace